STUDY THE IMPACT OF THE RESEARCH ORIENTATION PROGRAM ON UNDERSTANDING THE BASICS OF RESEARCH AMONG UNDERGRADUATE MEDICAL STUDENTS - CS, RAJESH; PATIL, PRABHAKAR R; GAVIMATH, NEETA T (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: This study was conducted to evaluate the impact of research orientation program on understanding the basics of research among undergraduate medical students. Basic knowledge of research is required to prepare a research protocol. Methods: A research orientation program was conducted for enhancing the basic knowledge/skills of research for preparing a research protocol for short-term research projects. This basic knowledge of research among the undergraduate students was determined by using a set of questionnaire. The participants were given a set of questionnaire before and after attending the research orientation program. Results: It was observed that the participated candidates improved their skills between the pretest and posttest which is due to well planned workshop/research orientation program. Conclusion: This study indicates these kind of research orientation program could help undergraduate students for enhancing the research skills required for preparing research protocol of short term research projects.